Association of low birthweight and small for gestational age with maternal ferritin levels: A retrospective cohort study in China - Tao, Yun; Kang, Jiawei; Liu, Juan; Duan, Jie; Wang, Fang; Shi, Yue; Li, Yujuan; Wang, Cheng; Xu, Dan; Qu, Xinlan; Guo, Juanjuan; Ma, Jianhong; et al. (Frontiers in Nutrition, 2022)
Background: Birthweight have profound impacts on health status throughout lifetime, however, the relationship between maternal ferritin level in pregnancy and birthweight of the newborn remains controversial. Objective: This retrospective cohort research was to analyze the associations between maternal ferritin levels during pregnancy with birthweight outcomes, primarily for low birthweight (LBW) and small for gestational age (SGA). Methods: Newborns weighing lower than 2500 grams were defined as LBW. SGA is defined as birthweight lower than the 10th percentile of the distribution of newborns’ birthweight of the same gestational age. Multivariable logistic regressions have been used to explore the associations of maternal ferritin levels and birthweight related outcomes, in which the ferritin concentration was logarithm transformed in the model. We further used restricted cubic spline models to explore linear/nonlinear dose–response manners of ferritin level and birthweight outcomes. Results: A total of 3566 pregnant women were included in the study. In the results of the present study, we observed that maternal ferritin levels were linearly associated with the risk of LBW (p trend =0.005) and SGA (p trend=0.04), with the adjusted odd ratios (ORs) of 1.78 (95% CI 1.37-2.32) for LBW and 1.87 (95% CI 1.38-2.54) for SGA with an increase in Ln-ferritin concentrations per unit. The adjusted ORs across quartiles of ferritin levels were 2.14 (95% CI 1.03-4.47) for Quartile 2, 3.13 (95% CI 1.47- 6.69) for Quartile 3, and 3.63 (95% CI 1.52-8.68) for Quartile 4 for LBW. The adjusted ORs of LBW and SGA among women using supplemental iron were 0.56 (95% CI 0.38, 0.85) and 0.65 (95% CI 0.40, 1.05) compared with nonusers, respectively. Conclusions: Our findings found a linear dose–response relationship between ferritin levels and an increased risk of poor birthweight outcomes, suggesting that maternal ferritin level during pregnancy may provide an additional predictor for differentiating poor birthweight related outcomes. Further exploration should be conducted to ensure maternal ferritin thresholds and iron supplement doses.